A Middle School's Response-to-Intervention Journey: Building Systematic Processes of Facilitation, Collaboration, and Implementation. (March 2013) - Dulaney, Shannon K.
This article discusses a qualitative case study examining one middle school's response to intervention (RtI) efforts. Study participants included the principal, assistant principal, and members of the school's leadership team. A description of the RtI consensus and infrastructure-building processes, consideration of the RtI facilitators, and a review of the accomplishments and barriers to implementation they encountered are provided.